Pulmonary Metastasis from Pseudomyxoma Peritonei - Toshiyuki Kitai (Gastroenterology Research and Practice)
Pseudomyxoma peritonei (PMP) is a rare clinical condition, where copious mucinous ascites accumulate in the peritoneal cavity due to dissemination of mucin-producing tumor. Because of this disseminating, yet nonmetastasizing, behavior, PMP attracts much interest from surgical oncologists in that aggressive locoregional therapy can give the opportunity of long survival and even cure. Although extra-abdominal metastasis is exceptionally rare, the lung is the most likely site in such a case. In this paper, the clinical findings and treatment of eleven cases with pulmonary metastasis from PMP were reviewed, including ten cases in the literature and one case which we experienced. The clinical features of PMP cases with pulmonary metastasis were similar to cases without pulmonary metastasis. The histological type was low-grade mucinous neoplasm in most cases. Pulmonary lesions were resected in seven cases in which abdominal lesions were controlled by cytoreductive surgery and hyperthermic intraperitoneal chemotherapy or another therapeutic modality. Disease-free state was maintained in five cases at the end of the follow-up period. However, it should be noted that rapid progression after resection was seen in two cases, suggesting that biological features may have changed by surgical intervention.